Phylogenetic origin of two Japanese Torreya taxa found in two regions with strongly contrasting snow depth - Aizawa, Mineaki; Worth, James R. P. (Journal of plant research, 2021)
The Japanese archipelago exhibits a notable difference in snow depth in winter, deep snow on the Sea of Japan side and low snow cover on the Pacific Ocean side. This contrasting pattern has shaped the distribution of infraspecific taxon pairs in a range of woody plants, with taxa found on the Sea of Japan side typically exhibiting a stunted shrub form with multiple decumbent stems. The phylogenetic origin of these taxon pairs is unknown, i.e., whether the two taxa diverged from the same species or if they have different origins. This study aimed to reveal the phylogenetic origin of two varieties of Torreya nucifera (Taxaceae); var. nucifera is a tree found on the Pacific Ocean side, whereas var. radicans is a shrub found on the Sea of Japan side. We examined the phylogenetic relationships of the two varieties and worldwide Torreya taxa using whole chloroplast genomes, chloroplast DNA fragments, and the nuclear ribosomal internal transcribed spacer (ITS). The whole chloroplast genome phylogeny indicated that T . nucifera var. radicans was a sister taxon to Chinese T . grandis , rather than to var. nucifera . In contrast, the nuclear ITS phylogeny indicated that while several haplotypes of T . nucifera var. radicans were closely related to T . grandis , most haplotypes of T . nucifera var. radicans formed a single clade with those of var. nucifera . This implies that the homogenization of the ITS has occurred between the two taxa, while taxon-specific chloroplast DNA haplotypes were retained. These discordant phylogenies suggested that the two taxa have different phylogenetic origins, but have an intricate evolutionary history, involving inter-taxa hybridization and gene flow, possibly when their distributions were confined to sympatric refugia. Given the genetic evidence and distinct difference in growth form, we propose that T . nucifera var. radicans should be taxonomically treated as a distinct species, T . fruticosa .